Health care ethics : a Catholic theological analysis - Ashley, Benedict M. (Georgetown University Press, 2006)
Health Care Ethics is a comprehensive study of significant issues affecting health care and the ethics of health care from the perspective of Catholic theology. It aims to help Christian, and especially Catholic, health care professionals solve concrete problems in terms of principles rooted in scripture and tested by individual experience; however, its basis in real medical experience makes this book a valuable resource for anyone with a general interest in health care ethics. This fifth edition, which includes important contributions by Jean deBlois, C.S.J., considers everyday ethical questio.